PENGARUH STRATEGI PEMBELAJARAN AFEKTIF TERHADAP MORAL SISWA KELAS VIII DI SMP NEGERI 4 LAGUBOTI KABUPATEN TOBA SAMOSIR TAHUN PEMBELAJARAN 2019/2020 - Sarma Sinvia Hasugian (IAKN Tarutung, 2020)
AbstractThis study aims to determine the effect of affective learning strategies on student morale. This research uses inferential quantitative approach. The population is all students of class VIII Laguboti Middle School 4 who are Protestant Christians totaling 151 people. Sampling using a purposive sampling technique that is class VIII A totaling 30 people. This research instrument is a closed questionnaire. Analysis results value rcount = 0,493rtable=0,361 dan tcount=2,997ttable 2,042 shows that there is a relationship between affective learning strategies with student morals and obtaining the significance of simple regression equation that . This study concludes that the influence of affective learning strategies on moral is 24.3 %.Hypothesis test obtained Fcount=9,00Ftable =2,09 then H0 is rejected and Ha is accepted. The author provides input for Christian religious education teachers to improve affective learning strategies so that student morale improves. Keywords: Affective learning strategies, student morale